(untitled) (International Journal of Environmental Sciences, 2025)
Due to rising environmental concerns and the shift towards sustainable lifestyles, consumers’ preference is shifting towards organic food products. Simultaneously, social media influencers have emerged as powerful marketing media, capable of influencing consumer behaviours. This study conceptualizes influencer authenticity through four key dimensions-expertise, sincerity, trustworthiness, and uniqueness and investigates how perceived authenticity of social media influencers shapes consumer well-being, purchase intention and actual consumption behaviour in the organic food sector. In order to achieve this, a well-structured questionnaire was administered to 253 urban and educated respondents belonging to Delhi-NCR region. The data was analysed using SPSS and SmartPLS-4. Structural equation modelling (SEM) was employed to test the validity of proposed model. The results show that all four authenticity dimensions significantly impact consumer well-being, which in turn has a positive impact on purchase intention. In addition to this, purchase intention emerged as a strong predictor variable of actual consumption behaviour in case of organic food consumption. These findings contribute to existing literature by establishing a strong linkage between influencer authenticity, consumer well-being and consumption behaviour. Practical implications for marketers and policymakers include designing trust-based social media influencer campaigns in the organic food sector.